The right to a view in Russia: History, legislation and future prospects - Polina N. Andreeva (RUDN Journal of Law)
The right to a view in Russia, rooted in Roman law, remains underdeveloped in contemporary Russian legislation and legal scholarship. The study aims to investigate the legal status of the right to a view, identifying its unique characteristics, methods of protection and guarantees in the Russian Federation. The author examines the historical aspects, the legislative framework surrounding this right, and its aesthetic and economic implications. A dialectical approach is employed alongside formal-legal methods, comparative analysis, and others. The findings indicate that current legislation lacks legal guarantees for preserving views from windows, as evidenced by judicial practice. The right to a view is neither explicitly defined nor protected by specific norms in Russian Law. Nonetheless, the relevance of issues related to views is increasing due to ongoing urbanization and territorial development. The current landscape reveals significant legal gaps that hinder the protection of property owners’ interests. The author concludes that the right to a view necessitates further study and legislative regulation to ensure its protection in today’s context.